Chinggis khan and his conquest of Khorasan: causes and consequences - Ara, Aniba Israt; Islam, Arshad (Lap Lambert Academic Publishing, 2013)
This book explores the causes and consequences of Chinggis Khan's invasion of Khorasan in the 13th century. It discusses Chinggis Khan's charismatic leadership qualities that united all nomadic tribes and gave him the authority to become the supreme Mongol leader, which helped him to invade Khorasan. It also focuses on the rise of the Muslim cities in Khorasan where many Muslim scholars kept their intellectual brilliance and made Khorasan the cultural capital of the Muslims. This study apprises us of Chinggis Khan's war tactics and administrative system which made his men extremely strong and advanced despite their culture remaining barbaric in nature. His progeny also followed a similar policy for a long time until all Muslim cities were fully destroyed. The work also focuses on the rise of many sectarian divisions among the Muslims which brought disunity that eventually led to their downfall. Thus, this study underscores the importance of revitalization of unity in the Muslim world so that Muslims may not become vulnerable to any foreign imperialistic power. Unity also is the key to preserve Muslim intellectual thought and Islamic cultural identities.